Pengaruh Emotional Branding dan Brandimage terhadap Customer Loyalty Produk Teh Gelas pada Gen Z di Kota Bandung - Shaqina Yunika Dewi; Terra Saptina Maulani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the responses of Gen Z regarding the influence of Emotional Branding and BrandImage on Customer Loyalty of Teh Gelas products among Gen Z in Bandung, both partially and simultaneously. The intense competition in the packaged tea drink market, along with the consistent decline in Teh Gelas brand index, the changing lifestyle, and consumption patterns of Gen Z, highlight significant challenges for Teh Gelas in maintaining customer loyalty. Additionally, negative consumer reviews on social media further weaken the BrandImage of Teh Gelas. The research method used is quantitative with a descriptive and verificative approach, and data collection was carried out through the distribution of questionnaires to 100 respondents. The analytical instruments include validity testing, reliability testing, classical assumption testing, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, t-test (partial), f-test (simultaneous), correlation coefficient testing, and coefficient of determination analysis, with the help of SPSS Version 30 software. The research results show that the significance level of f is 0.01, which is smaller than 0.05. Therefore, H_03 is rejected, which means that Emotional Branding and BrandImage have a simultaneous effect on Customer Loyalty of Teh Gelas products among Gen Z in Bandung.